Large Language Model Method as a Translator Indonesian Into SQL Language - Putra, Candra; Arlis, Syafri; Nurcahyo, Gunadi Widi (Universitas Putra Indonesia YPTK Padang, 2025)
The development of information technology has encouraged the massive implementation of information systems and web-based applications in various sectors, including in the academic environment. However, one of the challenges that are still often faced is the difficulty in extracting or mining information from databases flexibly without having to create additional report modules or write SQL code manually. This problem becomes an obstacle for non-technical users, such as administrative staff or lecturers, who need certain data quickly from academic information systems. In this paper, it is intended to convert Indonesian commands into SQL queries automatically, without the need to add additional programming code. Along with advances in Natural Language Processing (NLP) and Machine Learning technology with the Large Language Model (LLM) method, there is now a new approach that allows users to interact with databases only through commands in natural language. The case study was conducted on the Academic Information System of UIN Padangsidimpuan using a dataset of 1,500 student data. The focus of the research is on the type of Data Query Language (DQL) query in Indonesian form, which is then translated by the model into a SQL command to obtain the desired data. The results showed that this approach was able to achieve results with a Rouge1 conversion precision rate from 0.03 to 0.89. This shows that the integration of LLM technology in academic information systems has great potential in improving data accessibility, operational efficiency, and supporting data-driven decision-making faster and more intuitively, especially for users who do not have a technical background.